2020
DOI: 10.1111/jcmm.16129
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circEIF4G2 aggravates renal fibrosis in diabetic nephropathy by sponging miR‐218

Abstract: Circular RNAs play essential roles in the development of various human diseases. However, how circRNAs are involved in diabetic nephropathy (DN) are not fully understood. Our study aimed to investigate the effects of circRNA circEIF4G2 on DN. Experiments were performed in the db/db mouse model of type 2 diabetes and NRK‐52E cells. We found that circEIF4G2 was significantly up‐regulated in the kidneys of db/db mice and NRK‐52E cells stimulated by high glucose. circEIF4G2 knockdown inhibited the expressions of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Furthermore, we revealed the adsorption relationship between circITSN2 and miR-218-5p. It is reported that miR-218-5p could be absorbed and regulated by many circRNAs, like circEIF4G2 (Lin et al, 2020;Xu et al, 2020) and circSAMD4A (Wei et al, 2020). Our research also identified a novel upstream circRNA sponge for miR-218-5p in chicken muscle development.…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, we revealed the adsorption relationship between circITSN2 and miR-218-5p. It is reported that miR-218-5p could be absorbed and regulated by many circRNAs, like circEIF4G2 (Lin et al, 2020;Xu et al, 2020) and circSAMD4A (Wei et al, 2020). Our research also identified a novel upstream circRNA sponge for miR-218-5p in chicken muscle development.…”
Section: Discussionsupporting
confidence: 54%
“…28 , 29 , 30 , 31 , 32 Growing evidence suggested that circRNAs play crucial roles in cell functions such as cell metabolism, differentiation, proliferation, apoptosis and invasion. 19 , 33 , 34 , 35 , 36 Increasing studies showed that circRNAs involved in the development of many diseases including cancers, neurological diseases, congenital diseases, intervertebral disc degeneration and endocrine diseases. 37 , 38 , 39 , 40 , 41 , 42 , 43 Recently, studies indicated that circRNAs also play important roles in osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…Danshen is a very valuable herb in Chinese traditional medicine. It has been reported that Danshen has the antioxidant, anti-inflammatory and antibacterial activities 53 . The anti-inflammation efficacy of Danshen is generally played by the main biological activities in it, such as Salvianolic acid B, tanshinone IIA, Danshensu and dihydrotanshinone I 54 .…”
Section: Discussionmentioning
confidence: 99%